Extremely low‐profile wideband array antenna using TCDA with polarization convertor. Issue 3 (22nd October 2020) - Kim, Seongjung; Nam, Sangwook
Abstract: Herein, an extremely low‐profile and wideband array antenna is proposed whose height is 0.03 λ low at the lowest operating frequency. The development of the proposed array antenna is described, and its performance is compared with those of conventional patch arrays, stacked patch arrays, planar ultrawideband modular antenna arrays, and tightly coupled dipole arrays (TCDAs). Furthermore, the impedance bandwidth is 98.2% at broadside radiation, and the overlapped bandwidth when scanning up to 30° is 95.9%. This high figure of merit is obtained by introducing a polarization convertor. Finally, the measured active VSWR and array gain of the fabricated 6 × 6 array antenna are discussed. The measured result is in good agreement with the simulated result.